Pelvic insufficiency fracture in an osteoporotic 47-year-old female: a case report - Mehta, Chandan; Lalwani, Devansh; Shaikh, Ashraf Fazal; Desai, Mohan Madhav (International Journal of Research in Orthopaedics, 2024)
Insufficiency fractures (IFs) represent a form of stress fractures frequently linked to osteoporosis and a lack of vitamin D. These fractures, which are not caused by trauma, typically manifest in the pelvis and spine, although occurrences in atypical locations are also relatively frequent. The primary methods for diagnosing IF involve using plain radiographs and magnetic resonance imaging scans, which are commonly employed imaging techniques. The management involves both medical and surgical methods, tailored as per the needs of the patient. 47-year-old female patient presented to the outpatient department with complaints of low back ache with waddling gait, with pain not responding to analgesics. Laboratory and radiological assessment revealed osteoporotic Insufficiency fracture in the pelvis which was managed with both surgical and medical methods, with surgical management involving percutaneous screw fixation of the fractures. Diagnosis of the osteoporotic insufficiency fractures at atypical locations can be extremely challenging because of the inconclusive radiographs and the lack of a perceptible trauma history and hence, can be missed at the initial presentation. The management includes both operative and non-operative modalities, best tailored as per the patient needs and expectations.